Parking Area for People with Special Needs: Standard Design in Indonesia - Hadi Sudarjat (Universitas Pendidikan Indonesia (UPI), 2022)
The goal of this research is to describe the concept of a disabled parking lot. This study was based on an examination of the literature from a variety of sources, particularly those in Indonesia. The results of the research are collected, processed, and provided in the form of an easy-to-understand explanation. As a result, it is envisaged that the research findings can be utilized as a guide for architectural and environmental construction, particularly in hospitals, schools, and public facilities for persons with special needs (i.e. wheelchairs, crutches, and canes for the blind).